Response to: Responses of larval zebrafish to low pH immersion assay : Comment on Lopez-Luna et al. - Sneddon, Lynne U.; Steenbergen, Peter J. (The journal of experimental biology, 2017)
Lopez-Luna et al. (2017a) investigated the utility of using larval zebrafish as a replacement for adults in nociceptive testing. Five days post-fertilisation larvae were held in a 25-well plate and monitored using a video tracking system. Either larvae were undisturbed or system water was added